Preparation of graphene/Nile blue nanostructure on glassy carbon electrode: Decoration with platinum nanoparticles and application for electro-oxidation of methanol. (17th August 2016) - Karimi Shervedani, Reza; Amini, Akbar; Moetamedi Sedeh, Negar
Abstract: Well-dispersed Pt nanoparticles supported on Nile blue functionalized graphene nanosheets were successfully prepared on glassy carbon (GC-GNs-NB-Pt) electrode by a facile and effective two-step electrochemical method. Further electrode was fabricated where NB was formed and attached onto the surface in its polymer form (GC-GNs-NBpoly -Pt). The Pt decorated GNs-NB nanostructures were characterized by field-emission scanning electron microscopy (FESEM), energy dispersive X-ray diffraction (EDX) microanalysis, Raman spectroscopy and electrochemical methods. The results showed a three-dimensional nanostructure for Pt nanoparticles decorated onto the functionalized GNs-NB surface. The characterized electrodes were tested for electrochemical oxidation of methanol in H2 SO4 . A comparison between the synthesized electrodes; GC-GNs-Pt, GC-GNs-NB-Pt and GC-GNs-NBpoly -Pt, in terms of their electrochemical performance, revealed that the GC-GNs-NB-Pt benefits of a large and exceptional electrocatalytic activity for methanol oxidation. This improved activity could be attributed to the NB playing a crucial role in dispersing and stabilizing of Pt on GNs-NB platform. Highlights: Well-dispersed Pt nanoparticles are supported on GC/GNs functionalized with Nile blue. The GC-GNs-NB-Pt electrode is tested successfully for electrooxidation of methanol. The fabricated nanostructure exhibited excellent activity better than that observed for Pt/C. The enhanced activity is mainly attributed to the interaction between NB and GNs.